2020
DOI: 10.1016/j.vas.2020.100125
|View full text |Cite
|
Sign up to set email alerts
|

Myringotomy in dogs: Contamination rate from the external ear canal - a pilot study

Abstract: Highlights Sample collection via myringotomy is associated with a high contamination rate. The suitability of this method for detection of otitis media is questionable. Iatrogenic spread of pathogenic microorganisms into the middle ear is possible.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
17
0
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(20 citation statements)
references
References 34 publications
2
17
0
1
Order By: Relevance
“…In around one fifth of affected ears in this study, concurrent Malassezia OM was diagnosed based upon otoscopic findings and sampling of middle ear content. This procedure carries the potential for iatrogenic contamination of yeast from the ear canal into the tympanic cavity and thereupon false diagnosis of Mal OE/OM 33,34 . The frequency of Mal OE/OM in the present study, however, is comparable to reports of OM diagnosed in dogs with undefined, chronic OE using CT 35 and MRI 17 imaging.…”
Section: Discussionsupporting
confidence: 44%
“…In around one fifth of affected ears in this study, concurrent Malassezia OM was diagnosed based upon otoscopic findings and sampling of middle ear content. This procedure carries the potential for iatrogenic contamination of yeast from the ear canal into the tympanic cavity and thereupon false diagnosis of Mal OE/OM 33,34 . The frequency of Mal OE/OM in the present study, however, is comparable to reports of OM diagnosed in dogs with undefined, chronic OE using CT 35 and MRI 17 imaging.…”
Section: Discussionsupporting
confidence: 44%
“…In a study of normal canine cadavers, contamination with fluorescein‐stained saline from the horizontal canal was noted in 19 of 28 (68%) of the middle ears. There was positive bacterial growth in only one of 11 (9%) of the middle ears with corresponding external ears with positive cultures 10 . However, microbial contamination may have been rare in this study as these were normal ear canals that were first cultured, and then flushed and suctioned before myringotomy.…”
Section: Myringotomy Proceduresmentioning
confidence: 75%
“…There was positive bacterial growth in only one of 11 (9%) of the middle ears with corresponding external ears with positive cultures. 10 However, microbial contamination may have been rare in this study as these were normal ear canals that were first cultured, and then flushed and suctioned before myringotomy. If these ears had been infected, the microbial contamination rate may have been higher.…”
Section: Myringotomy Proceduresmentioning
confidence: 94%
“…The high contamination rate (67%) of MEC samples with material from EEC reported in a previous study by Reinbacher et al. (2020) using the traditional myringotomy technique might highlight the value of this novel technique in order to avoid MEC contamination.…”
Section: Discussionmentioning
confidence: 88%
“…It may lead to pressure reduction of the MEC, specimen collection for cytology and microbial cultures, and administration of drugs into the MEC ( Bruyette & Lorenz, 1993 ; Rose, 1977 ). In a previous study by Reinbacher, Kneissl, Hirt, Spergser and Panakova (2020) on canine cadavers free from otitis, specimens from the MEC sampled via video-otoscopically controlled myringotomy were contaminated with material from EEC in over 67% of cases. In this study, contamination of MEC aspirates was confirmed by the presence of fluorescent dye introduced into the EEC before aspiration.…”
Section: Introductionmentioning
confidence: 97%